HERMENEUTIKA OTENTISITAS HADIS M. MUSTOFA AZAMI - Lilik Faiqoh (Farabi, 2017)
This article discusses Azami criticism to Ignaz Gholziher and Joseph Schacht. The author tries to integrate the relations of hermeneutics as a solution to solve the issues of Hadith authenticity, and its interconnected to psychology, that Azami position when criticizing the Orientalists, Joseph Schacht, based on the flow of his thought of isnaad. Then in reviewing hermeneutics, in general there are three dominant element is the relationship between (author), Text (text) and readers (reader). So the results of this analysis, the author is orientalist, Joseph Schacht Ignaz Goldziher. The Text is orientalist books, thoughts, opinions or their theories, in this case Joseph Schacht. The reader is referred Azami. The discovery of the authors that position Azami criticism included are the internal and external criticism, namely external criticism Azami focus lies in criticism of the Orientalists, he criticized Joseph from isnaad. And internal criticism, plays on historiography, he criticized the use of sciences related to hadith, such as ‘Ilm Tadwin al-Hadith, ‘Ilm Rijal al-Hadith, ‘Ilm Jarh wa ta'dil, Ulum al-Hadith, ‘Ilm al-Fiqh.